2017
DOI: 10.1002/osp4.95
|View full text |Cite
|
Sign up to set email alerts
|

The effect of characteristics of proteins fed during gestation and lactation on development of metabolic syndrome in dams and male offspring of Wistar rats

Abstract: SummaryObjectiveThe objective of the study is to examine the role of characteristics of proteins in maternal and weaning diets on risk of metabolic syndrome in male offspring.MethodsPregnant Wistar rats were allocated to two groups (n = 12) and were fed the AIN‐93G diets based on either intact protein‐based diet (IPD) or mixed amino acid‐based diet (AAD) from day 3 of gestation throughout gestation and lactation. Male offspring were weaned to either an IPD or AAD diet for 18 weeks.ResultsIn dams, AAD group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 61 publications
0
14
1
Order By: Relevance
“…According to Słupecka et al 17 , the breastfeeding phase places a high energetic demand on dams, which is accompanied by an increase in food and, consequently, caloric intake. Jahan-Mihan et al 18 found similar results for the body weight of dams treated with AIN93-G diet. From the middle of the second week of treatment, the dams began to lose weight.…”
Section: Breastfeeding Period (D0-d21)mentioning
confidence: 61%
“…According to Słupecka et al 17 , the breastfeeding phase places a high energetic demand on dams, which is accompanied by an increase in food and, consequently, caloric intake. Jahan-Mihan et al 18 found similar results for the body weight of dams treated with AIN93-G diet. From the middle of the second week of treatment, the dams began to lose weight.…”
Section: Breastfeeding Period (D0-d21)mentioning
confidence: 61%
“…After 12 h fasting overnight, blood samples were drawn from the tail vein at fasting and 15, 30, and 60 min after a glucose administration (0.375 g glucose per mL, 5 g glucose per kg BW). 25 Blood pressure Systolic (SBP) and diastolic blood pressure (DBP) were measured by a non-invasive tail-cuff method (optical plethysmography) using a tail manometer tachometer system (BP-2000, Visitech system; Apex, NC, USA). After an adaptation process (5-day adaptation period), rats were restrained in holders on a constant warm platform (30 °C).…”
Section: Glucose Tolerance Testmentioning
confidence: 99%
“…On the day of measurement, five mock measurements preceded a series of ten measurements that were used to calculate the average as reported previously. 25 Blood glucose Tail vein glucose concentration was assessed using test strips using a handheld commercial glucometer (Contour ® Next Blood Glucose Meter, Bayer Healthcare LLC, Mishawaka, IN, USA). The accuracy and variance of the glucometer and test strips were examined by applying control solutions (levels 1 and 2) provided by the manufacturer (Bayer, Bayer Healthcare LLC, Mishawaka, IN, USA).…”
Section: Glucose Tolerance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggested that the satiating effect of whey protein may be related to its specific amino acid composition . 67 However, the timing of the measurement (120min) might be too late since whey protein is a fast protein and in many studies, its effect was more significant within 1hour after administration. In another study, the effect of intact whey protein and amino acid-based diets fed during pregnancy and lactation on body weight, food intake and intake regulatory hormones in both mothers and their offspring of Wistar rats was tested.…”
Section: Regulation Of Food Intake Satiety and Protein Synthesismentioning
confidence: 99%